Development of an automated solar photovoltaic tracking system / Ahmad Maliki Omar, Sulaiman Shaari and Abdul Rahman Omar - Omar, Ahmad Maliki; Shaari, Sulaiman; Omar, Abdul Rahman (2006)
This research involves the design and development of a prototype product code-named SolT 2A is a system that tracks the position of the sun automatically across the celestial vault in two axes. This kind of system is typically used in a solar photovoltaic (PV) system in terrestrial applications as well as extra-terrestrial applications such as spaceships and satellite systems to provide electrical power. It is designed and fabricated due to two main problems: a) Malaysia is located in the equator, thus the solar altitude crosses the zenith and the azimuth reverses direction; and b) Malaysia has a space programme that requires the use of solar PV power for its space satellites and probably later-on spaceship technology. These main problems require the use of a two axes solar tracking system. In addition, so far, Malaysia has not implemented such power-tracking systems. Thus SolT 2A has been designed and fabricated to address these problems. SolT 2A uses a combination of electro-mechanical devices with an element of programming ingenuity and intelligence. Basically SolT 2A measures solar irradiance at four points and makes comparisons in terms of the intensity received. These data are then analysed and processed by the microcontroller before being sent to a DC motor system that ensures the maximum amount of solar irradiance received on the PV panels. Thus SolT 2A is a system that maximises the power output of the PV panels to obtain the highest power output at all times. With the technical know-how and proven prototype, Malaysia can look into joining the small and limited but niche pool of expertise in this area. This will not only give immediate socio-economic impact to the population, but will give an upgrade to Malaysia as a country with expertise in the area. In addition, Malaysia has committed interest in upgrading and modernising her defense systems, and with further testing and improvement, Solt 2A system can be further upgraded to reach a commercial stage. This will definitely be of commercial interest to the country.